Cybertrespass - Graham, Roderick (Cybercrime and digital deviance, 2024)
This chapter discusses cybertrespass (hacking). Few topics in cybercrime have experienced the variance in perception as cybertrespass, having been perceived as both a relatively harmless means of exploring the boundaries of digital infrastructures and the most egregious of violations into one's personal domain. Designations of ownership and access rights hold much weight with this topic, and the reader is challenged to expand their perception of territoriality into the digital landscape. By doing so, it should become clear how the invasion of digital space is indeed an act both in and of itself a serious infraction and a gateway to additional violations (e.g., data theft, data manipulation, compromising functionality of operating systems).